REBRANDING CV. PRAWARA DWI PERSADA SEBAGAI UPAYA MENCIPTAKAN BRAND AWARENESS - Rizal, M Faizal; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: CV. Prawara Dwi Persada is a company that runs in the field of architecture and interior design. This newcomer company that runs in business of architecture, need an effort to build a strong identity and image in order to create brand awareness of the company. Then, the act of rebranding as an effort to create brand awareness with the creation of a new identity and promotional media such as a logo for the company, stationery sets, print ads, and website is necessary. The purpose of this final assignment is to rebranding CV. Prawara Dwi Persada which will adjust the vision and mission of the company and provide a fresh visual appearance than previous branding. To be able producing draft and appropriate design, it takes several stages such as interviews, observation, data collection, the creative strategy from CV. Prawara Dwi Persada and then continued to the process of designing. The keywords that has been obtained from these stages is the "treasure". This final assignment report produces logo, print media advertising, stationery sets, and a website, which will be submitted to the company owner of CV. Prawara Dwi Persada.Â Â Keywords: Rebranding, Brand Awareness, Promotion, CV Prawara Dwi Persada